Pharmacological Review of Caralluma r.br: A Potential Herbal Genus - Ratnakaram, Dr. Venkata Nadh (Asian Journal of Pharmaceutics (AJP), 2019)
In history, medicinal plants were proven as a source of active compounds with therapeutic applications, and at present, they are an important collection for the discovery of novel drug leads. Caralluma is a genus used as traditional medicine. The present article thoroughly reviewed about the classification of Caralluma into subgenera, number of its species, its distribution in different parts of the world, and pharmacological activities exhibited by different species of Caralluma.